Microgastrinae (Hymenoptera: Braconidae) parasitizing Epirrita autumnata (Lepidoptera: Geometridae) larvae in Fennoscandia with description of Cotesia autumnatae Shaw, sp. n. - Ruohomäki, Kai; Klemola, Tero; Shaw, Mark; Snäll, Niina; Sääksjärvi, Ilari; Veijalainen, Anu; Wahlberg, Niklas (Entomologica Fennica, 2013)
The microgastrine subset of hymenopteran parasitoids of the geometrid Epirrita autumnata is investigated in Fennoscandia. Ecology, including population dynamics, of the moth has been intensively studied in northern and mountainous Finland, Norway and Sweden. Recently supported hypotheses about the causes of its cyclic population dynamics stress the role of parasitoids, while the parasitoid complex with some 15 species is insufficiently known. The complex includes four solitarymicrogastrine species, Protapanteles anchisiades (Nixon), P. immunis (Wesmael), Cotesia salebrosa (Marshall) and C. autumnatae Shaw, sp. n. Here, we provide detailed figures for the latter, which is morphologically close to C. jucunda (Marshall), and describe the species as new to science. We also providemore general habitus figures of the other three species, as well as an identification key for the four species, aiming to aid recognition of these species by ecologists dealing with microgastrine parasitoids of E. autumnata and their alternative geometrid hosts.